Validity of 3D Reconstructed Computed Tomographic Image in Using Craniometrical Measurements of the Skull for Sex Differentiation (An Iraqi Study) - Sadeq, Noor M; Fatah, Ahlam A (Journal of Baghdad College of Dentistry, 2015)
Background: The skull offers a high resistance of adverse environmental conditions over time, resulting in the greater stability of the dimorphic features as compared to other skeletal bony pieces. Sex determination of human skeletal considered an initial step in its identification. The present study is undertaken to evaluate the validity of 3D reconstructed computed tomographic images in sex differentiation by using craniometrical measurements at various parts of the skull. Materials and Method: 3D reconstructed computed tomographic scanning of 100 Iraqi subject, (50 males and 50 females) were analyzed with their age range from20-70 years old. Craniometrical linear measurements were located and marked on both side of the 3D skull images. Results: For the all parameters measured for sexes the mean value for Male had significantly greater than females with (p value < 0.001). A receiver operating characteristic curves was obtained for each variable to observe their overall performance in sex determination. The area of mastoid triangle was found the best variable in sex differentiation (ROC area =0.97 for unilateral skull measurements and 0.98 for bilateral measurements).while EU-EU was found to be the least one. Conclusion: 3D reconstructed Computed tomography scanning is a good diagnostic method for analyzing the craniometrical measurements of sex determination. sex differentiation for isolated part of the skull when only the fragmentary crania is available, could be achieved and the highest accuracy in sex determination can be obtained whether part or complete skull available.